1997
DOI: 10.1097/00000539-199702000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Desflurane and Isoflurane During Closed-Circuit Anesthesia with Spontaneous and Controlled Mechanical Ventilation

Abstract: Although theoretical models predict uptake of inhaled anesthetics during closed-circuit anesthesia (CCA), clinical data for most anesthetics are conflicting or non-existent. In addition, the effects of patient characteristics and mode of ventilation on anesthetic uptake are unclear. Forty-one ASA physical status I or II adult patients undergoing a variety of 1-1.5 h surgical procedures were randomly allocated to receive CCA with desflurane or isoflurane with ventilation being either spontaneous or controlled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Inter-individual variation is also a factor affecting uptake kinetics. [478] On plotting the infusion requirements over time, we found that it varied for similar Et-Iso in different patients [Figure 4]. This can be due to individual differences in the factors determining uptake i.e., CO, blood/gas partition coefficient (λ B/G ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inter-individual variation is also a factor affecting uptake kinetics. [478] On plotting the infusion requirements over time, we found that it varied for similar Et-Iso in different patients [Figure 4]. This can be due to individual differences in the factors determining uptake i.e., CO, blood/gas partition coefficient (λ B/G ).…”
Section: Discussionmentioning
confidence: 99%
“…[19] Hence, it may be difficult to predict completely what is happening in vivo . [7] Brody's equation has been derived from a large ‘normal’ sample population under resting conditions. It does not necessary predict the output for the individual patient and might be different from the measured CO in clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale behind the practice is illustrated in figure 3. However, it has been noted (Westenskow et al 1983, Hendrickx et al 1997 that the unit dose method tends to overestimate the amount of anesthetic agent needed and so lead to the administration of more agent than is desired. The analysis here would suggest that this occurs due to use of the Severinghaus relationship from time zero, and from the misconception of the underlying compartmental pharmacokinetics that we have demonstrated arises from that.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that if this analysis were performed with high-potency volatile inhalational anesthetics with low fat solubility and therefore short fat time constant, further discrimination might be possible during anesthetics of 100 min duration. Such analysis would have to be based upon empirical studies of the uptake of these high-potency agents (Hendrickx et al 1997, 2003, Yasuda et al 1991a, 1991b rather than using the Severinghaus data for nitrous oxide.…”
Section: Discussionmentioning
confidence: 99%
“…they tested the model, they compared its behavior with Lowe's square root of time (Lowe andErnst 1981, da Silva et al 1997), implying that this simpler empirical relationship is the standard against which models should be measured. Much of this was reviewed by Hendrickx et al (1997Hendrickx et al ( , 2003Hendrickx et al ( , 2004. That all the compartmental models discussed above have rapid uptake in the early phase and slow uptake in later phases suggests that they have a behavior similar to the original multi-exponential model as well as the inverse square root of time model.…”
Section: Introductionmentioning
confidence: 99%